Analisis Kebutuhan Pengembangan Bahan Ajar Digital Fisika Berbasis Project Based Learning Terintegrasi Pendekatan STEM - Selma Riyasni; Intan Purnama Yani; Widia Kemala Sari; Zulhendra Zulhendra (Journal on Education, 2023)
21st century learning is suggested to be based on information and communication technology, for example using digital teaching materials. The learning model used is an innovative learning model that improves students' 21st century skills such as project based learning which is also suggested in the independent curriculum. The use of project based learning learning models is considered effective if it integrates the STEM approach. The initial step in developing STEM-integrated PjBL-based digital teaching materials is to conduct an analysis of the needs of teachers and students. The purpose of this study is to describe the results of the analysis of the needs for the development of digital teaching materials based on the integrated PjBL learning model with the STEM approach. The subjects of this study were 22 physics teachers and 50 students of SMAN 2 Bukittinggi. Data collection through questionnaires, then analyzed to obtain conclusions. The conclusions from this study show 1) learning still does not use digital teaching materials, 2) it is necessary to develop teaching materials based on the PjBL learning model that is integrated with STEM to assist student project assignments.